Beginning REALbasic - Ford, Jerry Lee (Apress, 2012)
Welcome to Beginning REALbasic! REALbasic is a programming language that provides you with everything you need to create software applications that can run on Macintosh, Windows, and Linux. REALbasic is an extremely powerful programming language that is capable of creating world-class software. Yet, at the same time, REAlbasic is easy to learn and makes a perfect programming language for first-time programmers. Using REALbasic, you can create applications, utility programs, and computer games. If you are a Windows programmer, REALbasic provides you with all the tools you need to write just about any Windows application imaginable: the same goes for Macintosh and Linux programming. By supporting cross-platform application development, REALbasic significantly enhances your ability to distribute your applications. This means you can share your work with more friends and colleagues, and if you are in the business of developing commercial software, REALbasic can help you attract new consumer markets.